Structural brain lesions in schizophrenia -magnetic resonance imaging on a mid field magnet - S R Parkar; R Seethalakshmi; H Shah (Indian Journal of Radiology and Imaging, 2006)
Objectives : The brain damage associated with schizophrenia has been established beyond doubt; however, what remains unexplored is the biological nature of transcultural variations. An important reason for this was the lack of mid and high field scanners in developing countries like India. Material and Methods : We undertook a pilot study using a 0.5 Tesla MRI scanner (General Electric Signa Contour) to explore identifiable structural brain lesions in ten randomly selected individuals with schizophrenia. Results: Nine of the ten participants in the series had structural brain changes. The most common findings were ventricular dilatation and prominent cerebral cortical sulci and cerebellar folia. Additionally non-focal white matter lesions were observed in three patients and small right hippocampus was noted in one participant. Conclusions : The study discusses that establishing structural brain lesions with mid field scanners is indeed feasible. The small study sample and heterogeneity of schizophrenia however made it difficult to establish any definite associations